Mexicans in Wisconsin - González, Sergio M., 1987- (Wisconsin Historical Society Press, 2017)
"Beginning with the arrival of the first large wave of agricultural and industrial workers in the early 1920s, Wisconsin's Mexican community has played an integral role in the state's cultural, social, economic, and religious history. Although some came as migrant laborers who worked as seasonal workers and then returned to their homes and families in Mexico, a large number of Mexican immigrants settled across the state's cities and rural towns and in the process developed vibrant communities. Arriving after the settlement of most European-origin immigrants, Mexicans strove to carve out their own space in Wisconsin and its unique immigrant history. This manuscript will endeavor to tell both the story of those who came and those who stayed to make Wisconsin their home. Unlike many other immigrant groups, especially those from Europe, who witnessed a sharp decline in immigration beginning in the 1920s, Mexican immigration to Wisconsin has continued and grown to the present day. With communities across Wisconsin, ranging from Milwaukee to Wautoma to Green Bay to La Crosse, Mexicans have become integral members of the state's various communities, culture, and economies. Today, Mexicans rank as the third largest race or ethnicity category in Wisconsin, trailing only Non-Hispanic whites and Non-Hispanic Blacks. Despite having a sizable presence in Wisconsin since the 1920s, however, manuscript-length writing regarding the state's Mexican community has been limited. This manuscript will contribute to the growing field of historical research documenting this nearly century old community."--Provided by publisher.